Arctigenin hinders the invasion and metastasis of cervical cancer cells via the FAK/paxillin pathway - Dan Liao; Yanyan Liu; Cuifen Li; Bin He; Guanghui Zhou; Yejia Cui; Haohai Huang (Heliyon, 2023)
Context: Cervical cancer is the most common gynecological pernicious tumor with high morbidity and mortality worldwide, especially in developing countries. Arctigenin (ARG), a nature-derived component, has exhibited anti-tumor activity in various tumors. Objective: To explore the effect of ARG on cervical cancer. Materials and methods: The effect and mechanism of ARG on cervical cancer cells were explored by cell counting kit-8 (CCK-8), flow cytometry, transwell and Western blot assays. Additionally, in vivo experiment was conducted in xenografted mice by immunohistochemistry (IHC), terminal deoxynucleotidyl transferase deoxyuridine triphosphate (dUTP) nick end labeling (TUNEL) and Western blot assays. Results: ARG treatment induced both concentration-dependent and time-dependent reductions in the cell viability of SiHa and HeLa cells with a IC50 value of 9.34 μM and 14.45 μM, respectively. ARG increased the apoptosis rate and the protein levels of cleaved-caspase 3 and E-cadherin, but decreased the invaded cell numbers and the protein levels of Vimentin and N-cadherin in vitro. Mechanically, ARG inhibited the expression of focal adhesion kinase (FAK)/paxillin pathway, which was confirmed by the overexpression of FAK in SiHa cells. The inhibitory role of overexpression of FAK in proliferation and invasion, as well as its promoted role in apoptosis were reversed with ARG treatment. Meanwhile, ARG suppressed growth and metastasis, and enhanced apoptosis in vivo. Consistently, ARG administration reduced the relative protein level of p-FAK/FAK and p-paxillin/paxillin in tumor tissues of xenografted mice. Conclusion: ARG inhibited proliferation, invasion and metastasis, but enhanced apoptosis of cervical cancer via the FAK/paxillin axis.